A Simple Strategy to Prepare Colloidal Cu‐Doped ZnSe(S) Green Emitter Nanocrystals in Aqueous Media. (28th April 2014) - de S. Viol, Lívia C.; Raphael, Ellen; Bettini, Jefferson; Ferrari, Jefferson L.; Schiavon, Marco A.
<x xml:space="preserve">Abstract</x> A novel and simple method is described for preparing colloidal Cu‐doped ZnSe(S) quantum dots (QDs) in aqueous media by introducing copper ions using the same method as to prepare colloidal ZnSe(S). More specifically, the Cu‐doped ZnSe(S) are prepared through the nucleation‐doping method in the presence of 3‐mercaptopropionic acid as stabilizers using zinc perchlorate, copper sulphate, and NaHSe as precursors. Confirmation of the preparation of Cu‐doped ZnSe(S) nanocrystals (NCs) is done with absorption and emission spectroscopies (UV–vis and PL) as the QDs show intensive green emissions. The reduction of ions Cu2+ to Cu+ is confirmed by using electron paramagnetic resonance (EPR), in which Cu+ ions are silent. The size determination is performed by using transmission electron microscopy (TEM) and dynamic light scattering (DLS), resulting in Cu‐doped ZnSe(S) particles with a mean diameter of 4.6 ± 3.5 nm. The excellent stability observed for the nanoparticles overcomes the intrinsic instability of traditional aqueous Cu‐doped ZnSe(S) NCs.